Analisis perencanaan pengadaan bahan baku bokar untuk menghasilkan pallet pada PT. Perkebunan Nusantara V Bukit Selasih - Firsal Dwi Pratomo; Liswar Hamid; Rio J.M. Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to determine how much raw material requirements needed in the future, by using several methods of forecasting time series model (time series), which will be selected the most effective method for forecasting the need for raw materials. In addition, this study also discusses the factors that influence the procurement of raw materials to the PT. Perkebunan Nusantara V Bukit Selasih. The data were obtained by direct observation keperusahaan the research object, namely, PT. Perkebunan Nusantara V Bukit Selasih and interviews with the parties the company is with the leadership and some of the workers. Based on the results of the research method of time series model (time series) performed least squares trend and the trend of the moment. Both methods have the results and the same value of MAD, then it can be inferred from that of some existing methods in forecasting time series model, it has the same result but with a different way of working. It was concluded that the right forecasting method to forecast the need for raw materials bokar at. PT. Perkebunan Nusantara V Bukit Selasih is the method of least squares trend and the trend of the moment method for calculation of the results of these two methods have the forecasting results and the same value of MAD.Keywords: Planning, time series models (time series).